Quantitative determination of volatile organic compounds formed during Polylactide processing by MHS-SPME. (February 2017) - Salazar, Rómulo; Domenek, Sandra; Plessis, Cédric; Ducruet, Violette
Abstract: Polylactide (PLA), a bio-based polyester, has been used in wide applications including food packaging. Nevertheless, it is well known that mass transfer occurs between packaging polymer and foodstuff leading to safety and quality issues. In this sense, volatile organic compounds (VOCs) present in packaging materials can migrate to the food in contact, changing its sensorial properties. Up to date, no study has focused on quantification of VOCs in PLA during its processing, which needs an optimized methodology to measure compounds at very low concentrations. In this study, different PLA samples in form of pellets, extruded films and thermoformed samples were studied in order to determine the VOCs present in each step of processing and to quantify them using headspace extraction methodology (MHS-SPME). Several volatile organic compounds were determined such as aldehydes, ethanol, acetone, acetic acid and lactides. Among the VOCs identified, three compounds were quantified: acetaldehyde; 2-methyl-2-propanol; 2, 3-pentanedione. Acetaldehyde and 2, 3-pentanedione increased after the extrusion and then decreased or disappeared after thermoforming. The results showed that residual acetaldehyde in PLA could be an important marker for the industry in the selection of PLA grades.